Frailty as a mediator between sleep quality and cognitive impairment among the rural older adults: a cross-sectional study - Ping Dong; Cheng Cheng; Wenqiang Yin; Ziyuan Li; Yongli Shi; Min Gao; Xiaona Li; Dongping Ma; Hongwei Guo; Yan Wei; Zhongming Chen (BMC Geriatrics)
Abstract Background Cognitive impairment is a common health problem among older adults. Previous studies have proven the association between sleep quality and cognitive impairment, but the specific underlying mechanisms need to be further explored. This study aimed to examine the relationship between sleep quality and cognitive impairment and the mediating effect of frailty in this relationship among the rural older adults. Methods Data from a cross-sectional study conducted in rural areas of Shandong Province from September to December in 2023. A total of 695 rural older adults were included. The Pittsburgh Sleep Quality Index (PSQI) was used to measure sleep quality. Frailty was defined using the FRAIL scale. We assessed cognitive impairment using the Dementia Screening Interview (AD8). Logistic regression analyse was used to assess the relationship between sleep quality and cognitive impairment. And the Karlson-Holm-Breen (KHB) method was performed to test the mediating role of frailty in this relationship. Results After adjusting for all covariates, sleep quality was significantly associated with cognitive impairment (OR = 1.047, 95% CI: 1.005—1.090). Frailty mediated the relationship between sleep quality and cognitive impairment, with a mediation effect value of 0.010 (95% CI: 0.001—0.020), accounting for 17.86% of the total effect. Conclusions We found there was an association between sleep quality and cognitive impairment, and frailty mediated the above relationship. Comprehensive intervention measures should be taken to reduce the incidence of frailty in the older adults and to improve their sleep quality, thereby preventing and delaying the occurrence and development of cognitive impairment.